MOLD PROPERTIES OF INDONESIA NATURE SAND AS GREEN SAND - Yusup Hendronursito; Muhammad Amin; Kusno Isnugroho; David Candra Birawidha (Majalah Ilmiah Pengkajian Industri, 2019)
The mould properties of Juwono sand, were investigated. The samples were subjected to various physical and mechanical test. These include permeability, green compression strength, and chemical composition by XRF/ XRD analysis. Green shear strength, grain shape, water content, and clay content were also carried out on the samples. Juwono sand casting containing 32.76% clay and category in grade 212/75 of fine sub grades were found to posses adequate permeability, good strength and refractoriness suitable for casting of both ferrous and non ferrous alloys.